Polyhydroxybutyrate (PHB) Production Using an Arabinose-Inducible Expression System in Comparison With Cold Shock Inducible Expression System in Escherichia coli - Napathorn, Suchada Chanprateep; Visetkoop, Sirirat; Pinyakong, Onruthai; Okano, Kenji; Honda, Kohsuke (Frontiers in Bioengineering and Biotechnology, 2021)
Cupriavidus necator strain A-04 has shown 16S rRNA gene identity to the well-known industrial strain C. necator H16. Nevertheless, the cell characteristics and PHA production ability of C. necator strain A-04 were different from those of C. necator H16. This study aimed to express PHA biosynthesis genes of C. necator strain A-04 in Escherichia coli via an arabinose-inducible expression system. In this study, the PHA biosynthesis operon of C. necator strain A-04, consisting of three genes encoding acetyl-CoA acetyltransferase (phaAA-04, 1182 bp, 40.6 kDa), acetoacetyl-CoA reductase (phaBA-04, 741 bp, 26.4 kDa) and PHB synthase Class I (phaCA-04, 1770 bp), was identified. Sequence analysis of the phaAA-04, phaBA-04 and phaCA-04 genes revealed that phaCA-04 was 99% similar to phaCH16 from C. necator H16. The difference in amino acid residue situated at position 122 of phaCA-04 was proline, whereas that of C. necator H16 was leucine. The intact phaCABA-04 operon was cloned into the arabinose-inducible araBAD promoter and transformed into E. coli strains Top 10, JM109 and XL-1 blue. The results showed that optimal conditions obtained from shaken flask experiments yielded 6.1±1.1 g/L cell dry mass (CDM), a PHB content of 93.3±0.9% (w/w) and a productivity of 0.24 g/(L·h), whereas the wild-type C. necator strain A-04 accumulated 78% (w/w) PHB with a productivity of 0.09 g/(L·h). Finally, for the scaled-up studies, fed-batch cultivations by pH-stat control in a 5-L fermenter of E. coli strains XL1-Blue harboring pBAD/Thio-TOPO-phaCABA-04 and pColdTF-phaCABA-04 in MR or LB medium, leading to a PHB production of 31.4±0.9 g/L with a PHB content of 83.0±3.8% (w/w), a CDM of 39.3±1.2 g/L, a YP/S value of 0.39 g PHB/g glucose and a productivity of 1.9 g PHB/(L·h) using pColdTF-phaCABA-04 in MR medium. In addition, PHB production was 29.0±1.1 g/L with 60.2±2.3% PHB content in the cell dry mass (CDM) of 51.2±1.0 g/L, a YP/S value of 0.21 g PHB/g glucose and a productivity of 1.4 g PHB/(L·h) using pBAD/Thio-TOPO-phaCABA-04 in MR medium. Thus, a relatively high PHB concentration and productivity were achieved, which demonstrated the possibility of industrial production of PHB.